A comparative study of ecotourism development between Indonesia and Madagascar Case studies: mount ciremai and andasibe mantadia national parks - Hidayat Putro, Heru Purboyo; Onjaharimanana, Rakotonindrina (Opción)
It is increasingly recognized that large-scale of tourism is increasing nowadays, and has significant negative impacts on the natural environment or the community of the target tourist regions. Related to this problem, ecotourism is one of alternative that often proposed. This study compares two National Parks of two different countries, Mount Ciremai National Park for Indonesia and Andasibe Mantadia Park for Madagascar, to find out how the results of the application of ecotourism. The results showed that the two parks are Eco touristic even in the case of the Mount Ciremai National Park which is not yet certified as an ecotourism.